Abusive Supervision and Workplace Incivility in Public Sector Hospitals in Khyber Pakhtunkhwa: Does Emotional Intelligence matter? - Majeed, Hafiz Adnan; Jan, Dr. Farzand Ali; Shah, Dr. Fayaz Ali (The journal of contemporary issues in business and government, 2021)
The key purpose of the very research is to highlight the role and significance of abusive supervision, workplace incivility and emotional intelligence in the health sector of Pakistan. A questionnaire survey was used to collect data from 302 respondents from health sector in KpK. Stratified sampling with proportionate allocation method of probability sampling technique was used by the scholars. Exploratory factor analysis and structure equation modeling were used to analysis the collected data. Results of the study demonstrate a strong positive link between all the three dimension of abusive supervision (i.e. anger active abuse, passive abuse, and humiliations active) and workplace incivility. The results further suggest that emotional intelligence play a moderating role in the relationship between abusive supervision and workplace incivility, such that with high emotional intelligence the strong effect of abusive supervision weaken on workplace incivility. Practical and theoretical contributions of the study was highlighted with suggestions for future research were given at the end of the paper.